Self-compassion mediates treatment effects in MDMA-assisted therapy for posttraumatic stress disorder - Gabrielle Agin-Liebes; Richard J. Zeifman; Jennifer M. Mitchell (European Journal of Psychotraumatology)
Background: Posttraumatic stress disorder (PTSD) is a severe condition often complicated by co-occurring disorders, such as major depression, alcohol use disorder, and substance use disorders. A well-powered phase 3 randomized, placebo-controlled trial has shown that MDMA-assisted therapy (MDMA-AT) may be an effective treatment for severe PTSD. However, the psychological mechanisms driving the therapeutic effects of MDMA-AT remain unclear. One potential mechanism is self-compassion, which is commonly conceptualized as a balance between compassionate self-responding (CS) – encompassing self-kindness, common humanity, and mindfulness – and uncompassionate self-responding (UCS) – encompassing self-judgment, isolation, and over-identification.Objective: This secondary analysis aimed to explore whether MDMA-AT enhances aspects of self-compassion and if changes in self-compassion mediate the therapy's effectiveness in reducing PTSD severity, depressive, and alcohol and substance use symptoms.Method: Eighty-two adults diagnosed with severe PTSD participated in a double-blind trial comparing three sessions of either MDMA-AT or placebo combined with therapy. Measures of PTSD severity, depressive symptoms, alcohol and substance use, and self-compassion were collected at baseline and 18 weeks later.Results: MDMA-AT led to statistically significant improvements in both UCS and CS. Significant improvements were also observed across all six subscales of the Self-Compassion Scale, including self-kindness, self-judgment, common humanity, isolation, mindfulness, and over-identification, most with large effect sizes. Changes in UCS and CS significantly and fully mediated the effects of MDMA-AT compared to placebo plus therapy in reducing PTSD severity and depressive symptoms. Findings were not significant for alcohol and substance use outcomes.Conclusions: These findings suggest that self-compassion may play a critical role in the therapeutic effects of MDMA-AT. Further research is needed to investigate the role of self-compassion in MDMA-AT to refine and develop more targeted, effective interventions for individuals with PTSD and co-occurring depression.